Current recommended management of tuberculosis. Issue 10 (19th October 2018) - Rogers, Benedict; Kennedy, Matthew; Wiselka, Martin; Morris, Thomas; Venkatraman, Navin
Abstract : Despite reductions in overall case numbers both globally and in the UK, tuberculosis (TB) remains a major health problem. Here, the authors discuss the pathogenesis of TB and important aspects of management, alongside recent developments in epidemiology, diagnostics and treatment.